May 22-24, 2017 Kuala Lumpur (Malaysia) ICLTET-2017, ACBES-2017 2017
DOI: 10.15242/iie.e0517022
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Stab and Spike Resistance Performance of Shear Thickening Fluids (STF) Impregnated Fabrics

Abstract: Abstract-This paper provides a brief review on relevant literature related to shear thickening fluids (STF) impregnated fabrics on stab and spike resistance performance. Soft body armours consist of multiple layers of high performance fabric to stop stab and spike threats. To reduce the number of fabric layers on soft body armours, STF has been introduced. STF transforms from liquid state to a solidlike state under applied stress and return to its original state after stress is removed. Hence, several studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Similarly, it has reported that particle shape has significant effects on drilling fluid properties such as fluid loss and rheological behaviors [24]. Whereas rods and plate shaped sharp-edged particles by jamming and interlocking can cause quick thickening [25] in fluids, flow would be negatively affected. Nanospherical polymeric particles would build viscosity less aggressively, in addition to enhancement of rheology (Figure 5).…”
Section: Polymeric Nanoparticles: Properties Shapesmentioning
confidence: 99%
“…Similarly, it has reported that particle shape has significant effects on drilling fluid properties such as fluid loss and rheological behaviors [24]. Whereas rods and plate shaped sharp-edged particles by jamming and interlocking can cause quick thickening [25] in fluids, flow would be negatively affected. Nanospherical polymeric particles would build viscosity less aggressively, in addition to enhancement of rheology (Figure 5).…”
Section: Polymeric Nanoparticles: Properties Shapesmentioning
confidence: 99%